Pembiasaan Asmaul Husna Sebagai Strategi Revitalisasi Karakter Religius Siswa: (Studi Kualitatif di SMK Batik 1 Surakarta) - Luqman Hakim; Mohamad Ali (Jayapangus Press, 2026)
The religious character of Vocational High School (SMK) students faces serious challenges amidst globalization and digitalization, leading to a decline in discipline, politeness, and religious consciousness. This condition demands character education strategies that transcend cognitive aspects, focusing instead on internalizing religious values through sustainable habituation. This study aims to analyze the implementation of Asmaul Husna (The 99 Names of Allah) recitation as a strategy to revitalize the religious character of students at SMK Batik 1 Surakarta. It emphasizes the roles of leadership and teacher supervision in maintaining habituation sustainability and maps its impact on students' religious character within the SMK context.Using a qualitative approach with a case study design, data were collected through observation, in-depth interviews, and documentation. The data were then descriptively analyzed through reduction, display, and conclusion drawing. The results indicate that the routine and structured habituation of Asmaul Husna, supported by teacher leadership and supervision, successfully fosters a consistent school religious culture. Positive impacts are observed in improved student discipline, politeness, religious awareness, emotional stability, and social concern. However, program implementation still faces obstacles such as time management constraints, varying levels of students' Arabic literacy, infrastructure limitations, and the risk of activities becoming mere formalities without deep reflection on their meaning. This research contributes to the development of a school leadership-based religious habituation model relevant for vocational education environments.